Children’s Internalizing Symptoms: The Role of Interactions between Cortisol and Respiratory Sinus Arrhythmia - El-Sheikh, Mona (2011)
We examined interactions between children’s physiological activity across two systems, the hypothalamic-pituitary-adrenal (HPA)-axis and the parasympathetic nervous system (PNS), as predictors of child-reported internalizing symptoms (depression, anxiety). HPA activity was indexed by baseline salivary cortisol, and PNS activity was indexed by baseline respiratory sinus arrhythmia (RSA). Study 1 consisted of 57 children (54% girls; M age = 8.81 years ±.34), and Study 2 included 219 children (51% girls; M age = 9.31 years ±.79). Cortisol interacted with RSA to explain unique variance in children’s internalizing symptoms. Across the two studies, children with higher cortisol levels in conjunction with higher RSA levels tended to exhibit the lowest levels of depression and anxiety symptoms. Findings demonstrate that contemporaneous consideration of physiological activity across multiple systems can advance understanding of internalizing symptoms in children.